Evaluation of the effectiveness of prophylactic strategies for cytomegalovirus infection in pediatric kidney recipients - O. M. Tsirulnikova; P. M. Gadzhieva; I. A. Miloserdov; D. A. Saydulaev; I. E. Pashkova (Вестник трансплантологии и искусственных органов)
Cytomegalovirus (CMV) infection is the most severe viral infection in renal transplant recipients, which can occur in the post-transplant period in both adult and pediatric recipients. Developing and applying an effective prevention and treatment strategy for pediatric renal graft recipients is a priority. Objective: to compare the effectiveness of the protocols used for the prevention of CMV infection in pediatric kidney transplant recipients.Materials and methods. The study enrolled 118 patients who underwent primary kidney transplantation at Shumakov National Medical Research Center of Transplantology and Artificial Organs. Based on retrospective analysis, all recipients were divided into two groups, depending on the prophylactic strategy after kidney transplantation. The followup period for pediatric kidney recipients ranged from 108 to 1803 (623.5 ± 379.5) days. CMV infection activity was monitored by polymerase chain reaction.Results. The frequency of CMV infection activation episodes at 3 and 6 months was independent of the prophylaxis strategy used. The recurrence rate of CMV infection one year after surgery was significantly lower (p = 0.037) with Strategy 2. No cases of CMV syndrome or CMV disease, graft dysfunction, or chronic rejection associated with CMV infection were reported. Increasing the dose of antiviral drugs in Strategy 1 did not increase the risk of cytotoxicity and nephrotoxicity, which are reversible (creatinine levels were not significantly different in the study groups at 3, 6, 12 months, p = 0.542, p = 0.287, p = 0.535, respectively). The incidence of kidney graft rejection did not increase in patients with lower doses of immunosuppressants in Strategy 2.Conclusion. Both prophylactic strategies are effective in pediatric kidney recipients. However, the choice of a strategy depends on the individual characteristics of the patient and requires a personalized approach.